World Christianity in Western Europe : diasporic identity, narratives and missiology - Olofinjana, Israel Oluwole (Regnum studies in mission., 2020)
"Christianity is a world religion with about 2.3 billion Christians. While World Christianity with its attention on the explosive growth of Christianity in Africa, Asia, Latin America, the Pacific and Oceania is definitely significant, it is also important to consider World Christianity as it is developing in Europe. This book investigates this phenomenon in Western Europe through the prisms of Diasporic Identity, migrant narratives and their mission theology. It considers the complex Christian identity of people migrating to Europe, their stories and mission praxis. Here is a book including contributors who are scholars and practitioners. These scholars and practitioners are Europeans as well as migrants from the Majority World (Africans, Caribbean, South Asia and Latin Americans) employing interdisciplinary approach, their work encompasses the fields of Diaspora Missiology, Practical Theology, World Christianity, Contextual Theology and Pentecostal Studies." - from the back cover.